Expressivism, pragmatism and representationalism - Price, Huw, 1953- (Cambridge University Press, 2013)
"Pragmatists have traditionally been enemies of representationalism but friends of naturalism, when naturalism is understood to pertain to human subjects, in the sense of Hume and Nietzsche. In this volume Huw Price presents his distinctive version of this traditional combination, as delivered in his Rene; Descartes Lectures at Tilburg University in 2008. Price contrasts his view with other contemporary forms of philosophical naturalism, comparing it with other pragmatist and neo-pragmatist views such as those of Robert Brandom and Simon Blackburn. Linking their different 'expressivist' programmes, Price argues for a radical global expressivism that combines key elements from both. With Paul Horwich and Michael Williams, Brandom and Blackburn respond to Price in new essays. Price replies in the closing essay, emphasising links between his views and those of Wilfrid Sellars. The volume will be of great interest to advanced students of philosophy of language and metaphysics"--